Adherence to the Mediterranean diet is associated with a reduced DAS28 index among patients with rheumatoid arthritis - Alawadhi, Balqees (2023)
BACKGROUND: Rheumatoid arthritis (RA) is a chronic, autoimmune disease that mostly affects the synovial joints. It has been hypothesized that dietary and other environmental and lifestyle factors contribute to the development of RA and its severity.OBJECTIVE: The present study aims to measure the effect of the Mediterranean diet (MedDiet) on the disease activity scores (DAS28) among patients with RA.METHODS: Adult patients who satisfied the American College of Rheumatology (ACR) classification criteria for RA from major hospitals in Kuwait were evaluated. A cross-sectional study conducted on 754 RA patients visits aged (21-79) years. Patients were evaluated using the DAS28. Patients' levels of adherence to the MedDiet are assessed using a validated 14-item Questionnaire (paper or web-based). The data was analyzed using both multivariate and univariate statistics. Multivariate logistic regression was used to analyze the statistical relationship between MedDiet and RA disease activity.RESULTS: The finding suggests that a MedDiet can have a positive impact on DAS28 among patients with RA. In the DAS28 cohort (DAS28 < 3.2, DAS28 ≥ 3.2), several Mediterranean survey components showed statistically significant differences. Patients with a Mediterranean score ≤ 5 was more likely to have hazard effects for DAS28 than those with a Mediterranean score of ≥10 (HR = 0.17, CI [0.08-0.37], p < .001). The finding shows that, Mediterranean levels ≤5, on biologics treatment, CRP, and patient global assessment were significantly associated with overall survival. Additionally, the MedDiet was found to be a significant predictor of DAS28 in the random forest decision tree plot, along with tender, RF, and creatinine. MedDiet patients had a lower DAS28 score than others.CONCLUSION: The findings suggest that optimal drug treatment and a restrictive diet can help to improve DAS28 score for patients with RA. More patients in the cohort DAS28 <3.2 used olive oil, servings of vegetables, fruits, and legumes. In contrast, more patients in the cohort DAS28 ≥ 3.2 consumed red meat, butter, sweetened or soft drinks, cakes, cookies, or biscuits, and tomato sauce.